Penguatan Karakter Toleran dalam Pembelajaran Bahasa Indonesia Berbasis Whole Language di Madrasah Ibtidaiyah - Ibda, Hamidulloh (Kopertais Wilayah X Jawa Tengah, 2018)
This article discusses the dynamics of intolerance from aspects of mind, language, action and solution through strengthening the education of tolerant character in learning Indonesian. Intolerance in practice can be harsh words, hate speech, harassment, until the action of radicalism. Strengthening character education is a mandate that must be implemented in Islamic elementary education. There are seventeen required implemented characters. Start religious character, honest, tolerant, disciplined, hard working, creative independent, democratic, curiosity, spirit of nationality, love of the homeland, appreciate achievement, communicative, love peace, love reading, caring environment, social care, and responsible. Tolerance became one of the urgent characters strengthened in this era of the fourth industrial revolution. The language of the children represents its character. The more polite, refined, and tolerant of their language, the stronger the character is polite, refined, and tolerant to them, and vice versa. Indonesian language learning with whole language approach can strengthen the tolerant character because it is done intact, integral, not partial from aspects of listening, reading, writing and speaking. The language understanding in this approach is not just textual, but contextual and even intertextual. Indonesian language learning through whole language approach aims to strengthen the character of tolerant, polite, social care and boils down to the attitude of religious tolerance. There are two indicators of religious tolerance, to people of fellow religion, and tolerance to people of different religions.